2013
DOI: 10.1007/s11999-012-2769-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Technique: Computer-generated Custom Jigs Improve Accuracy of Wide Resection of Bone Tumors

Abstract: Background Manual techniques of reproducing a preoperative plan for primary bone tumor resection using rudimentary devices and imprecise localization techniques can result in compromised margins or unnecessary removal of unaffected tissue. We examined whether a novel technique using computer-generated custom jigs more accurately reproduces a preoperative resection plan than a standard manual technique. Description of TechniqueUsing CT images and advanced imaging, reverse engineering, and computer-assisted desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 30 publications
6
70
1
1
Order By: Relevance
“…The result concurred with the accuracy of the two techniques reported in other clinical, sawbone or cadaveric studies [5,11,19,[22][23][24]. When we compared the accuracy between the two techniques in simulated pelvic bone resections, no statistical difference was noted.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The result concurred with the accuracy of the two techniques reported in other clinical, sawbone or cadaveric studies [5,11,19,[22][23][24]. When we compared the accuracy between the two techniques in simulated pelvic bone resections, no statistical difference was noted.…”
Section: Discussionsupporting
confidence: 90%
“…Although the planes of pelvic resection were different from those in this study, the pelvic sawbone study by Cartiaux et al [19,22] showed a similar trend of mean time required for the bone resection, 49 min for navigation assistance versus 6.9 min in PSI assistance. The greater operative time in the navigation group was due to the fact that time was required for the placement of patient tracker, system calibration and image-to-patient registration prior to the navigated bone resections.…”
Section: Discussionsupporting
confidence: 38%
See 1 more Smart Citation
“…Tumor patient-specific instruments (PSIs) were recently reported in bone tumor surgery [28•, 29•, 30]. This approach can achieve accuracy similar to that of navigational guidance, but it greatly reduces the operating time and can confine the bone saw along the planned plane of resection.…”
Section: What Are the Key Features Of Cats?mentioning
confidence: 99%
“…Reports by Wong et al [10,13] and Khan et al [11] have indicated that computer-assisted methods can improve the accuracy of resection of malignant bone tumors. Similarly, other authors have reported the utility of CAD for custom endoprosthesis construction [4,18,19].…”
Section: Introductionmentioning
confidence: 99%